The effects of online brand trust on e-satisfaction in low-cost carriers : a Singapore context. - Tan, Melvin Wei Yang. (2010)
The low-cost carrier (LCC) or budget airlines industry in Singapore has seen a dramatic increase in demand for its services from both leisure and business travelers. The purpose of this research is to explore the importance of online brand trust for the local LCC industry and its consequences, specifically in the area of e-satisfaction. It attempts to identify the most important antecedents of online brand trust and gives recommendations for LCC operators to further improve its relationships with its online customers.